The Simple Economics of Extortion: Evidence from Trucking in Aceh - Olken, Benjamin A.; Barron, Patrick (Journal of Political Economy, 2009)
This paper tests whether the behavior of corrupt officials is consistent with standard industrial organization theory. We designed a study in which surveyors accompanied Indonesian truck drivers on 304 trips, during which they observed over 6,000 illegal payments to police, soldiers, and weigh station attendants. Using plausibly exogenous changes in the number of checkpoints, we show that market structure affects the level of illegal payments. We further show that corrupt officials use complex pricing schemes, including third‐degree price discrimination and a menu of two‐part tariffs. Our findings illustrate the importance of considering the market structure for bribes when designing anticorruption policy.